Eucinetus linskyi, a new replacement name for preoccupied Eucinetus bicolor Lawrence, 2019, non Reitter, 1887 (Insecta: Coleoptera: Eucinetidae) - Lawrence, John F. (Zootaxa, 2021)
The species name Eucinetus bicolor Lawrence was proposed by Lawrence (2019, p. 155) for a new coleopteran species from eastern Victoria, Australia. However, this name was already used for the Palaearctic Eucinetus bicolor Reitter (1887, p. 514), currently combined as Nycteus bicolor (Reitter, 1887), and thus the names are primary homonyms according to ICZN Articles 53.3 and 57.2 (International Commission on Zoological Nomenclature 1999). To resolve this primary homonymy, in accordance with ICZN Article 60.3 (International Commission on Zoological Nomenclature 1999), Eucinetus linskyi is here proposed as a replacement name for Eucinetus bicolor Lawrence, 2019, non Reitter. This name is a patronym based on Marek Linský of Bratislava, Slovakia, who called my attention to this homonymy.